CTAB-GAN+: enhancing tabular data synthesis - Zhao, Zilong; Kunar, Aditya; Birke, Robert; Van der Scheer, Hiek; Chen, Lydia Y. (Frontiers in Big Data, 2024)
The usage of synthetic data is gaining momentum, in part due to the unavailability of original data due to privacy and legal considerations, and in part due to its utility as an augmentation to the authentic data. Generative Adversarial Networks (GANs), a paragon of generative models, initially for images and subsequently for tabular data, has contributed many of the state-ofthe-art synthesizers. As GANs improve the synthesized data increasingly resemble the real data risking to leak privacy. Differential privacy (DP) provides theoretical guarantees on privacy loss but degrades data utility. Striking the best trade-off remains yet a challenging research question. In this paper, We propose CTAB-GAN+ a novel conditional tabular GAN. CTAB-GAN+ improves upon state-of-the-art by (i) adding downstream losses to conditional GAN for higher utility synthetic data in both classification and regression domains; (ii) using Wasserstein loss with gradient penalty for better training convergence; (iii) introducing novel encoders targeting mixed continuous-categorical variables and variables with unbalanced or skewed data; and (iv) training with DP stochastic gradient descent to impose strict privacy guarantees. We extensively evaluate CTAB-GAN+ on statistical similarity and machine learning utility against state-of-the-art tabular GANs. The results show that CTAB-GAN+ synthesizes privacy-preserving data with at least 21.9% higher machine learning utility (i.e., F1-Score) across multiple datasets and learning tasks under given privacy budget.